Dampak Pemanfaatan Harta Pekerja Migran Indonesia Terhadap Hubungan Keluarga: Studi Kasus Di Desa Tanjung Mas Jaya - Yuliyani, Indri; Maki, Hud Leo Perkasa; Angkasa, Nawa; Irawan, Hendra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2025)
This study aims to determine and analyse the utilisation of assets earned by Indonesian migrant workers (PMI) and its impact on their relationships in Tanjung Mas Jaya Village, East Mesuji Subdistrict, Mesuji Regency. The method used was a descriptive qualitative approach with field research in the form of case studies. Informants were selected purposively based on certain criteria, including migrant workers, their spouses, parents-in-law, and neighbours who had relevant experience, particularly related to the misuse of migrant workers' earnings. Data collection techniques included primary data in the form of interviews and documentation, as well as a literature study from secondary sources. The results of the study show that (1) the assets earned by migrant workers are often used by their spouses without prior agreement, contrary to the intended purpose of sending funds, such as for children's education, home renovations, or business capital. The causes include a lack of communication, the absence of a written agreement, and the influence of social pressure and the consumptive lifestyle of spouses in their home country; (2) the impact of this misuse on family relationships, namely the emergence of domestic disharmony, divorce, and psychological effects on children.